1996
DOI: 10.1152/jappl.1996.81.1.413
|View full text |Cite
|
Sign up to set email alerts
|

Carotid artery blood flow and middle cerebral artery blood flow velocity during physical exercise

Abstract: Factors controlling cerebral blood flow (CBF) during exercise are complex and incompletely known. Different techniques have shown partly contradictory results of changes in regional and global cerebral perfusion during dynamic exercise in healthy subjects. To elucidate the global CBF response to supine stepwise increasing physical exercise, we measured blood flow in the left common carotid artery (QCCA) and the left internal carotid artery (QICA) simultaneously with the blood flow velocity in the ipsilateral m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

28
134
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(163 citation statements)
references
References 0 publications
28
134
1
Order By: Relevance
“…However, MCAv at 70 % HRR was similar or slightly reduced compared with that observed at 30 % HRR. This is in accordance with previous reports that the increase in MCAv is intensity dependent up until 60 % of V Á O2 max, after which it declines back towards resting levels due to hyperventilation-induced hypocapnia (Hellstrom et al 1996;Moraine et al 1993). Below ventilatory threshold, the increase in CBF with exercise is likely driven by increases in cerebral metabolism and PaCO 2 , as a result of increased functional activation with motor activity (Hellstrom et al 1996;Moraine et al 1993); however, above this, the large disproportional increase in ventilation reduces PaCO 2 and thus CBF despite progressive elevations in cerebral metabolism (Hellstrom et al 1996;Moraine et al 1993).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…However, MCAv at 70 % HRR was similar or slightly reduced compared with that observed at 30 % HRR. This is in accordance with previous reports that the increase in MCAv is intensity dependent up until 60 % of V Á O2 max, after which it declines back towards resting levels due to hyperventilation-induced hypocapnia (Hellstrom et al 1996;Moraine et al 1993). Below ventilatory threshold, the increase in CBF with exercise is likely driven by increases in cerebral metabolism and PaCO 2 , as a result of increased functional activation with motor activity (Hellstrom et al 1996;Moraine et al 1993); however, above this, the large disproportional increase in ventilation reduces PaCO 2 and thus CBF despite progressive elevations in cerebral metabolism (Hellstrom et al 1996;Moraine et al 1993).…”
Section: Discussionsupporting
confidence: 94%
“…This magnitude of increase is similar to that observed by other authors using transcranial Doppler to assess blood flow velocity in the MCA during exercise (Hellstrom et al 1996;Jorgensen et al 1992;Linkis et al 1995;Moraine et al 1993;Ogoh et al 2005). However, MCAv at 70 % HRR was similar or slightly reduced compared with that observed at 30 % HRR.…”
Section: Discussionsupporting
confidence: 90%
“…A comparable intensity of exercise was maintained across subjects by stipulating that oxygen consumption must be maintained at 40% of each subject's maximum. This intensity of exercise was chosen because a previous study 12 showed that it elicited the greatest change in cerebral blood perfusion. This is an intensity of exercise that can be achieved by the general population and, therefore, is a condition relevant to individuals with an intracranial aneurysm.…”
Section: Flow Computationmentioning
confidence: 99%
“…and Sheel 2007; Pott et al 1996;Hellstrom et al 1996;Madsen et al 1993;Ogoh et al 2005b). This increase is reflected with a parallel increase in regional CBF, neuronal activity and metabolism (reviewed in Ogoh and Ainslie 2009).…”
mentioning
confidence: 99%
“…In contrast, at least in young healthy subjects, CBF declines towards baseline values (Moraine et al 1993) when exercise intensity is >60% VO 2peak , regardless of the progressive increase in neuronal activity and metabolism. This reduction in CBF is attributed to increased cerebral vasoconstriction (Moraine et al 1993;Hellstrom et al 1996;Nybo and Rasmussen 2007) secondary to hyperventilatory-induced hypocapnia. This observation indicates that, during heavy exercise, CBF decreases despite progressive increases in cerebral metabolic demand (reviewed in Ogoh and Ainslie 2009).…”
mentioning
confidence: 99%